Insights Into Comparative Analyses and Phylogenomic Implications of Acer (Sapindaceae) Inferred From Complete Chloroplast Genomes - Yu, Tao; Gao, Jian; Liao, Pei-Chun; Li, Jun-Qing; Ma, Wen-Bao (Frontiers in Genetics, 2022)
Acer L. (Sapindaceae) is one of the most diverse and widespread plant genera in the Northern Hemisphere. It comprises 124–156 recognized species, with approximately half being native to Asia. Owing to its numerous morphological features and hybridization, this genus is taxonomically and phylogenetically ranked as one of the most challenging plant taxa. Here, we report the complete chloroplast genome sequences of five Acer species and compare them with those of 43 published Acer species. The chloroplast genomes were 149,103–158,458 bp in length. We conducted a sliding window analysis to find three relatively highly variable regions (psbN-rps14, rpl32-trnL, and ycf1) with a high potential for developing practical genetic markers. A total of 76–103 SSR loci were identified in 48 Acer species. The positive selection analysis of Acer species chloroplast genes showed that two genes (psaI and psbK) were positively selected, implying that light level is a selection pressure for Acer species. Using Bayes empirical Bayes methods, we also identified that 20 cp gene sites have undergone positive selection, which might result from adaptation to specific ecological niches. In phylogenetic analysis, we have reconfirmed that Acer pictum subsp. mono and A. truncatum as sister species. Our results strongly support the sister relationships between sections Platanoidea and Macrantha and between sections Trifoliata and Pentaphylla. Moreover, series Glabra and Arguta are proposed to promote to the section level. The chloroplast genomic resources provided in this study assist taxonomic and phylogenomic resolution within Acer and the Sapindaceae family.